Avgusta Danilova, interpretka ljudskih in umetnih pesmi na gramofonskih ploščah med identifikacijo, hibridizacijo in popularizacijo izročila - Golež Kaučič, Marjetka (Traditiones (Ljubljana), 2014)
The article focuses on the presentation of song and dramatic sound materials, recorded in the U.S.A. by Slovenian actress August Danilova. The 78 rpm gramophone records were published by gramophone companies Columbia in first two decades of 20th century. Our aim is to establish, on the basis of traditional and modern folklore and ethnological methods, and the theoretical discourses and analyses of songs and dramatic scenes, the most common genres of folk and literary songs on these recordings, and what kind of transformation of texts we can observe. At the same time we will be interested whether there are new models of cultural production and reproduction of Slovenian culture among emigrants in the United States.
Keywords: Danilova, Avgusta, 1869-1958; ethnology; etnomuzikologija; folk songs; literary songs; slovenske ljudske pesmi; umetne pesmi; gramophone records; zvočni posnetki; gramofonske plošče; zgodovinski pregledi